Pathological gambling in motion pictures; A systematic review - Kun Hwang; Yong Soon Choi; Yoo Chan Kim; Se Jin Hwang; Se Ho Hwang (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2020)
Background: The aim of this study is to analyze the movies of pathologic gambling from comprehensive samples. Methods: Movies (all 102 titles) related to gambling were collected by keyword search in IMDB (International Movie Database, www.imdb.com). Among them, 16 titles were selected in which the storyline was directly related to gambling, gambling scene was exposed in individual plots, and the result of gambling influenced the development of storyline. The films were reviewed and analyzed. Results: Protagonists were all males. The reasons why they first started gambling were mostly by temptation (46%). Purpose of their gambling act was to get rich (81%). Most of the gambling sites were casino (31%) or gambling house (25%). Most frequent type of gambling was poker (40%), followed by black jack (13%) and sports gambling (13%). Most of the gambling (63%) was illegal. In 56%, the gaming was temperate and the 42% was impulsive. In 67%, protagonist followed the gambling rule, but in 33%, he ran crooked gambling. In 57%, protagonist did not have any particular advantageous skill for gambling. In 2/3, the protagonist lost the game, won in 1/3. The protagonist was regretful for his gambling act in 45%. In 12 titles of 14 titles, 6 protagonist become happy irrespective of the result (2 win, 4 lose), but 6 became unhappy (1 win, 5 lose) (Odds ratio=2.5). Conclusion: How these people perceive 'gambling', from the exposed media information may be different from reality. We hope the result of this study might be helpful in education of gambling addicts.